Program Kelas Rawat Inap Standar (KRIS): Analisis Ekonomi Publik atas Pemerataan Layanan Kesehatan Nasional - Mely Nur Ratman; Nisa Nur Amanda; Suci Oktapia; Wahjoe Pangestoeti (CV. ITTC INDONESIA, 2025)
The Standard Inpatient Class Program (KRIS) is a health service reform policy that aims to eliminate the class 1, 2, and 3 systems in the National Health Insurance (JKN) inpatient services in order to create equal access and quality of services. This study aims to determine the effectiveness of government intervention through KRIS in the context of public economics, especially from the aspects of social justice, efficiency of resource allocation, and distribution of health services. The method used is a literature study with a descriptive-analytical approach that examines policies, official documents, and evaluation results from various institutions and previous studies. The results of the study indicate that although KRIS has improved service equality and patient satisfaction in a number of hospitals, there are still significant challenges in terms of infrastructure readiness, budget constraints, and resistance from service providers. The implications of this study emphasize the importance of sustainable funding support, strengthening technical regulations, and an inclusive transition strategy so that the KRIS policy can be implemented optimally and sustainably throughout Indonesia.